2022
DOI: 10.1002/cre2.660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the fracture resistance of the teeth prepared with ProTaper Universal, ProTaper Next, and ProTaper Gold rotary files

Abstract: Objectives: Root canal preparation can lead to cracks on the roots by creating stresses on the root canal walls, which decreases the fracture resistance of the tooth. The present study compared the fracture resistance of the teeth prepared by the ProTaper Universal (PTU), ProTaper Next (PTN), and ProTaper Gold (PTG) rotary file systems.Materials and Methods: Fifty-six single-canal premolar teeth were sectioned 14 mm from the root apex. The roots were standardized based on the buccolingual and mesiodistal diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…Protaper Gold has a convex triangular cross-section and an increased taper size. 8 Being in line with Milani et al, 21 who showed that all of the ProTaper systems did not show different fracture resistance, this study revealed that preparation with the ProTaper systems (PN and PG) did not affect the fracture resistance of the teeth. Nonetheless, the fracture resistance of the teeth prepared using both systems was lower than that using HC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Protaper Gold has a convex triangular cross-section and an increased taper size. 8 Being in line with Milani et al, 21 who showed that all of the ProTaper systems did not show different fracture resistance, this study revealed that preparation with the ProTaper systems (PN and PG) did not affect the fracture resistance of the teeth. Nonetheless, the fracture resistance of the teeth prepared using both systems was lower than that using HC.…”
Section: Discussionsupporting
confidence: 88%
“…A continuous vertical compressive force was applied at a crosshead speed of 1 mm/ min. 21 All the specimens were loaded until fracture. The maximum breaking loads by the universal testing machine were recorded in Newtons (N) with PC software connected to the loading machine.…”
Section: Methodsmentioning
confidence: 99%